OPERATION: THE PHENOMENON OF SOCIAL PRODUCTION AND ECONOMIC CONSCIOUSNESS - Khvorostiana, N. V. (Science and Transport Progress, 2007)
The terms of existence of exploitation are considered in public production and in consciousness of managing subject. The possible ways of overcoming of exploitation are resulted in economic consciousness of society.